(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
Banana (Musa) is a popular food crop globally, but diseases like Panama disease can cause serious damage to banana plantations. The resulting waste can be difficult for farmers to manage. To address this issue, there is an ongoing effort to create commercial paper bags using banana fibers from plantation waste. This method can reduce plant wastes from banana harvesting and decrease the use of plastic bags that pollute the environment. The results of the study in terms of ingredients, procedural process, durability, and presentation are highly acceptable according to chemical engineers and acceptable according to environmental engineers. It indicates that there is no significant difference between and among the assessments of the two groups of respondents in terms of ingredients, procedural process, durability, and presentation. The mean for the chemical engineers was 2.85, while the environmental engineers obtained 2.55. The variance obtained by chemical engineers is 2.544, while the variance obtained by environmental engineers is 2.088. The T-computed value is 0.316. T-critical is 2.306, with an alpha level of 0.05 and degrees of freedom of 8. Therefore, it accepts Ho. It indicates that there is no significant difference between the assessment of the two groups of respondents in terms of the aforementioned variables. To further enhance this project, it is recommended to gather the banana midrib beforehand and find sources to reduce production costs. Respondents suggested using adhesive, adding extra fabric layers, and using strong stitching materials such as nylon and polyester. Reinforcing the handles with additional stitching or doubling the fiber was also recommended. To make the product more attractive and fashionable, respondents suggested adding colors and an appealing design.